Team Assisted Individualization and Its Implications for Primary Level Students' Science Understanding - Ali Nurwidiyanto; Dewi Puji Rahayu; Eli Ngatripah (Edumaspul: Jurnal Pendidikan, 2023)
The obstacle faced at this time is that there are still many students who have difficulty in mastering material provided by the teacher in science learning in the classroom. One of the causes students have difficulty understanding learning material is that students less actively involved in learning. Therefore, this study aims to apply the corporative learning model with the TAI or Team Assisted Individualization type in an effort to improve students' understanding of natural science (IPA) materials or subjects. This research was a class action research, where the subject of this research was fourth grade students of SD Negeri 2 Merauke with a total of 32 students in the 2022/2023 school year. The implementation of this research was carried out for approximately two months starting from February to March, where there were 2 research cycles in total. In the process of data collection, this study applied observation and tests in each cycle. As the result, the implementation of science learning in elementary schools by applying one of the cooperative learning models, namely the Team Assisted Individualization type, proves that this model can improve students' understanding of science learning in class IV SD Negeri 2 Merauke based on the comparison of learning outcomes in each cycle, where Classical Completeness of cycle I was 69.68% and then increased in cycle II 88.90%.